Defining, constructing and policing a `New India' - Gopalakrishnan, Shankar (2006)
The advance of neoliberalism is seen to have either resulted from or accompanied the accession to power of repressive and socially reactionary political forces (as seen in the UK and the US of the 1980s). However, in understanding India of the 1980s and 1990s, the nature of the links between neoliberalism and the Hindu right does not appear entirely obvious. This article explores the deeper, common political goals and neoliberalism and Hindutva share. Such sharing does not represent a complete merger of these forces nor is it a purely opportunistic alliance. On the other hand, such alliances represent common class interests by articulating shared notions of a bounded, unitary and individual-based conception of society, as opposed to a community-based society. - Reproduced.
Keywords: Liberalism - India; Liberalism